Sculpting the soil microbiota. (22nd November 2021) - Custódio, Valéria; Gonin, Mathieu; Stabl, Georg; Bakhoum, Niokhor; Oliveira, Maria Margarida; Gutjahr, Caroline; Castrillo, Gabriel
SUMMARY: Soil is a living ecosystem, the health of which depends on fine interactions among its abiotic and biotic components. These form a delicate equilibrium maintained through a multilayer network that absorbs certain perturbations and guarantees soil functioning. Deciphering the principles governing the interactions within soils is of critical importance for their management and conservation. Here, we focus on soil microbiota and discuss the complexity of interactions that impact the composition and function of soil microbiota and their interaction with plants. We discuss how physical aspects of soils influence microbiota composition and how microbiota–plant interactions support plant growth and responses to nutrient deficiencies. We predict that understanding the principles determining the configuration and functioning of soil microbiota will contribute to the design of microbiota‐based strategies to preserve natural resources and develop more environmentally friendly agricultural practices. Significance Statement: We discuss here how physical aspects of soils influence its microbiota composition and how microbiota‐plant interactions support plant growth and its response to nutrient deficiencies.